2022
DOI: 10.1038/s41396-022-01229-4
|View full text |Cite
|
Sign up to set email alerts
|

Linking transcriptional dynamics of CH4-cycling grassland soil microbiomes to seasonal gas fluxes

Abstract: Soil CH4 fluxes are driven by CH4-producing and -consuming microorganisms that determine whether soils are sources or sinks of this potent greenhouse gas. To date, a comprehensive understanding of underlying microbiome dynamics has rarely been obtained in situ. Using quantitative metatranscriptomics, we aimed to link CH4-cycling microbiomes to net surface CH4 fluxes throughout a year in two grassland soils. CH4 fluxes were highly dynamic: both soils were net CH4 sources in autumn and winter and sinks in spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 84 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…A recent study, for instance, found that CH 4 fluxes were more strongly correlated with methanogenesis mRNA transcript abundances, but not with methanogen rRNA transcript abundances in grassland soils. 37 Supporting this, more studies showed stronger mRNA functional responses than rRNA taxonomic responses to environmental changes. 29,69,70 These results also support our previous finding that mRNA is the best proxy in revealing prokaryotic microbiome dynamics.…”
Section: ■ Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent study, for instance, found that CH 4 fluxes were more strongly correlated with methanogenesis mRNA transcript abundances, but not with methanogen rRNA transcript abundances in grassland soils. 37 Supporting this, more studies showed stronger mRNA functional responses than rRNA taxonomic responses to environmental changes. 29,69,70 These results also support our previous finding that mRNA is the best proxy in revealing prokaryotic microbiome dynamics.…”
Section: ■ Discussionmentioning
confidence: 84%
“…36 Recently, a new type of quantitative metatranscriptomics has been developed and validated, allowing us to infer absolute abundances based on total RNA content. 37,38 This approach, therefore, provides quantitative information and, thus, allows for accurately linking microbial dynamics to environmental processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Overall, even though DNA- and RNA-based meta-genomic techniques have provided insight into the microbiome compositions of soils, they may not relate well to ecosystem processes or functions. The relationship between the abundances of rRNA and mRNA of CO 2 -cycling microbes needs further study [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a great general need to build a predictive understanding of the ecological and evolutionary dynamics of microbial communities in the context of soil structure formation and mechanical stabilization (Rillig et al., 2017). The main challenges are the coupling of soil development or management‐induced soil changes with changes in the microbial habitat (soil microbiome) and the adaption of soil microorganisms at different time scales (e.g., Täumer et al., 2022). The evolution of microbial communities has not been considered, despite that these communities react within a few years to these changes in conditions (Udiković‐Kolić et al., 2012).…”
Section: Mechanistic Modelingmentioning
confidence: 99%